Effect of Na‐PDT and KF‐PDT on the photovoltaic performance of wide bandgap Cu (In, Ga)Se2 solar cells. (11th August 2020) - Zahedi‐Azad, Setareh; Maiberg, Matthias; Scheer, Roland
Abstract: Cu (In, Ga)Se2 solar cells exhibit higher efficiencies if an appropriate Ga gradient is introduced and if the absorber is doped with sodium (Na) plus a heavier alkali atom such as potassium. However, a Gallium gradient in the presence of Na is challenging because sodium impedes the interdiffusion of elements and influences the gradient. In this contribution, we show that the presence of sodium during growth with the combination of high Ga concentration creates a pronounced gradient that is detrimental for carrier collection. One solution is to avoid Na abundance during absorber growth but to add it to the grown absorber layer via a postdeposition treatment. We investigate the effect of different Na incorporation methods simultaneously with KF‐PDT on wide band gap CIGSe absorbers. By preparation on alkali‐free substrates and application of alkalis (NaF and KF) onto a grown CIGSe layer, we show by smoothening of the Gallium gradient a large improvement in the solar cell performance from 4% to 8%. Another way to optimize the gradient in the presence of Na is the modification of the three‐stage method. This yields the best efficiency of 10% in our laboratory at an integral GGI of ~0.8. By means of temperature‐dependent JV measurements, we show that the additional postdeposition of KF induces a barrier for the diode current. We conclude that KF‐PDT induces a new thin layer at the CIGSe surface that has a lower valence band edge relative to the CIGSe bulk and is responsible for the double‐diode behavior. This barrier can also explain the Voc (T) saturation at low temperature. Abstract : The presence of Sodium during film formation leads to a detrimental Gallium gradient in the Cu (In, Ga)Se2 layer. The Gallium gradient can be adjusted by a modified three‐stage coevaporation process. Potassium doping leads to efficiency improvement despite the formation of a surface layer (SL). The surface layer can explain device peculiarities such as a double‐diode and Voc (T) saturation.